PROSES ADOPSI INOVASI LIMBAH TERNAK MELALUI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. RAPP DI KAMPUNG OLAK KABUPATEN SIAK - Zulham Darmawan; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The process of adopting animal waste innovation into compost and biogas can improve the economy and welfare of the people of Kampung Olak. Through the Corporate Social Responsibility Program of PT. RAPP Estate Mandau seeks to assist the community in the process of adopting animal waste innovation so as to produce compost and biogas. With the presence of the adoption process of livestock waste innovation as a form of implementing the pillars of the mission of Siak Regency in Pillar 1 Creating the quality of human resources that are healthy, intelligent, moral, faithful and pious. The purpose of this study was to determine how the adoption of livestock waste innovation through the Corporate Social Responsibility (CSR) Program in Siak Regency and to determine the inhibiting factors for the adoption of livestock waste innovation through the Corporate Social Responsibility (CSR) program in Siak Regency. This research uses purposive sampling technique with qualitative research type using descriptive approach and the required data both primary and secondary data obtained through observation, interviews, and documentation then analyzed based on the research problem. The results of this study indicate that: first, the process of adopting the innovation of livestock waste through the Corporate Social Responsibility (CSR) program in Siak Regency in this study is the process of adopting the innovation of livestock waste running well. Second, the inhibiting factor is the ability of human resources, public insight, and capital.  Keywords : Innovation Adoption Process, Animal Waste, Corporate Social Responsibility